INVESTIGATION OF SEX-DEPENDENT EFFECTS OF CANNABIS IN DAILY CANNABIS SMOKERS - Cooper, Ziva D. (Drug Alcohol Depend, 2014)
BACKGROUND: Women exhibit an accelerated progression from first cannabis use to cannabis use disorder (CUD) and show pronounced negative clinical issues related to CUD relative to men. Whether sex-dependent differences in cannabis’ direct effects contribute to the heightened risk in women is unknown. This analysis directly compared cannabis’ abuse-related subjective effects in men and women matched for current cannabis use. METHODS: Data from four double-blind, within-subject studies measuring the effects of active cannabis (3.27–5.50% THC, depending on study) relative to inactive cannabis (0.00% THC) were combined for this analysis. Data from equal numbers of men and women from each study matched for current cannabis use were pooled (total n = 35 men; 35 women); cannabis’ effects were analyzed according to cannabis condition (active versus inactive) and sex. RESULTS: Active cannabis produced more robust subjective effects associated with abuse liability (‘Good,’ ‘Liking,’ ‘Take Again’) and intoxication (‘High,’ ‘Stimulated’) relative to inactive cannabis (p • 0.0001). Women reported higher ratings of abuse-related effects [‘Take Again’ and ‘Good’ (p • 0.05)] relative to men under active cannabis conditions but did not differ in ratings of intoxication. Active cannabis increased heart rate (p • 0.0001) equally for both sexes. CONCLUSIONS: The results from this study suggest that when matched for cannabis use, women are more sensitive to the subjective effects related to cannabis’ abuse liability relative to men, which may contribute to the enhanced vulnerability to developing CUD. Thus, sex is an important variable to consider when assessing the development of CUD.